PENGARUH PROFESIONALISME, KOMITMEN ORGANISASI, ETIKA PROFESI DAN PENGALAMAN AUDITOR PADA TINGKAT PERTIMBANGAN MATERIALITAS - Pratiwi, Veny Thama; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi, 2017)
Consideration of materiality is a professional judgment that affect the perception of the auditors on the needs of people who have sufficient knowledge and put our trust in the financial statements. Materiality relates to decision-making and related to the final results of the audit will be used by the user of the information. Research to determine the effect of professionalism, organizational commitment, professional ethics, and the auditor's experience on the level of materiality considerations in the public accounting firm in the province of Bali. Sampling technique used in this research was non probability sampling with purposive sampling method with the number of samples obtained in 49 samples. Data collection methods used in this study is a questionnaire that distribute questionnaires to the auditor in public accounting firm. The data analysis technique used to test the hypothesis in this research is the analysis of linear regression.
Keywords: professionalism, organizational commitment, professional ethics, and experience of auditor